An Optical Sensor for Volatile Amines Based on an Inkjet‐Printed, Hydrogen‐Bonded, Cholesteric Liquid Crystalline Film. Issue 5 (30th January 2014) - Stumpel, Jelle E.; Wouters, Claudia; Herzer, Nicole; Ziegler, Judith; Broer, Dirk J.; Bastiaansen, Cees W. M.; Schenning, Albertus P. H. J.
<x xml:space="preserve">Abstract</x> A printable hydrogen‐bonded cholesteric liquid crystal (CLC) polymer film is described, which can be used as a sensor for detection of gaseous trimethylamine (TMA). In this optical sensor the virgin CLC polymer network reflects green light. When anhydrous TMA gas penetrates the film, disruption of the hydrogen bonds occurs, with the simultaneous formation of carboxylate salts. The consequent reduction of the molecular order causes the green reflecting CLC film to become colorless. However, exposure to TMA in water‐saturated nitrogen gas results in a red reflecting film. Due to the hygroscopic nature of the polymer salt that is formed by TMA, water vapor which is present in the environment is absorbed by the films. This leads to swelling of the film, resulting in an increase in pitch size and therefore a red shift of the reflection band. Interestingly, after exposure to ambient conditions, restoration of the green reflecting film takes place, showing that the sensor can be used multiple times. In a proof of principle experiment, it was shown that these CLC films can be used as optical sensors to detect volatile amines, that are produced by decaying fish.